SELF-EFFICACY, PRECOMPETITIVE ANXIETY AND SELF-PERCEPTION OF PERFORMANCE IN UNDER 17 AND JUVENILE SOCCER PLAYERS - Segura Castro, Diego; Adanis Cerdas, Diego; Barrantes-Brais, Kristy; Ureña Bonilla, Pedro; Sánchez Ureña, Braulio (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2018)
Purpose: To analyze the relationships between self-efficacy, precompetitive anxiety, and self-perception of sports performance in two categories (under 17 and juvenile) of a Costa Rican soccer club. Methodology: 32 players participated in the study: 17 in the under 17 category (all 16 years of age) and 15 in the juvenile category (18.2 ± 0.77 years), with a mean overall age of 17.03 ± 1.23 years. Scales of general self-efficacy, precompetitive anxiety, specific self-efficacy and perception of performance were applied. Results: Under 17 players perceive their performance better compared to juvenile players. Somatic anxiety recorded a significant decrease (F(2, 46) = 10.21, p < .001) over time in both categories. Significant correlations (p < .005) were found between somatic anxiety and specific self-efficacy, somatic and cognitive anxiety, cognitive anxiety and specific self-efficacy, as well as between specific and general self-efficacy. Conclusion: The data show that players of both categories report similar results in most of the variables, there are significant correlations between some indicators, and there could be an adaptive capacity throughout the games evidenced in the decrease of somatic anxiety.